DC and AC side harmonics in CCC converters - Oliveira, Luis C. Origa de [UNESP]; Borges, Wilson M. [UNESP]; Souza, Julio B. de [UNESP]; Ravagnani, Lidia L. [UNESP] (IEEE, 2007)
The capacitor-commutated converter (CCC) has frequently been used in the conception of HVDC systems connected to busbars with low short circuit level. This alternative arrangement, in substitution to the conventional ones, guarantees less sensitive operational conditions to problems related with the commutation failure in the inverters besides supplying part of the reactive energy to be compensated. Studies related with its performance in steady and transient states have been presented in several works, however its behavior as harmonic source is still little explored. This work presents preliminary studies focusing the generation of characteristic harmonics by this type of converter. Subjects related with the amplification of the harmonic magnitudes are investigated and compared considering similar arrangements of conventional static converters (LCC) and CCC schemes. It is also analyzed the harmonic generation on the dc side of the installation and its influence on the ac side harmonics. The results are obtained from simulations in the time domain in PSpice environment and they clearly illustrate the operational differences between the L CC and the CCC schemes with regard to characteristic harmonic generation.
Keywords: commutation; CCC; converters; harmonics